Citizen participation in monitoring phytoplankton seawater discolorations. (July 2020) - Siano, R.; Chapelle, A.; Antoine, V.; Michel-Guillou, E.; Rigaut-Jalabert, F.; Guillou, L.; Hégaret, H.; Leynaert, A.; Curd, A.
Abstract: A citizen monitoring program ( Phenomer ) of marine water discolorations caused by high biomass phytoplankton development (Harmful Algal Blooms, HABs) was conducted in 2013, 2014 and 2015 in the coastal waters of Brittany (France). This project aimed to explore the feasibility of acquiring scientifically valuable data on water discolorations phenomena through a citizen science approach, extending the surface area of monitored coastal waters by means of citizen observations. During the three years of the project implementation, respectively 14, 32 and 28 warnings were sampled and recognized as phytoplankton water discolorations. Respectively, 7, 24 and 14 phenomena were observed outside of routine monitoring points. Citizen observations contributed towards evaluating the extension of red discolorations caused by Noctiluca scintillans and the duration and impact on marine fauna of green discolorations of Lepidodinium chlorophorum . A bivalve mortality event coincided with a dark-brown phytoplankton bloom characterized by the dominance of the toxic raphidophytes Heterosigma akashiwo and Pseudochattonella verruculosa, whose presence indicate a new potential hazard in Brittany. Interview analysis of citizen observations showed that the contributors to Phenomer are generally well-informed on environmental issues and concerned about the status of the marine environment. Phenomer demonstrates the complementary value of citizen science programs to routine phytoplankton monitoring, as well as providing scientific information on water discolorations phenomena, whose observations over a large territory have rarely been structured. The advantages and limits shown by the Phenomer project will help to optimize future applications of citizen science approaches for phytoplankton and HAB studies. Highlights: Phytoplankton seawater discolorations may be monitored by citizen observations. Citizen observations may complete routine phytoplankton monitoring networks. The surface area and duration of water discolorations have been evaluated. Interviews of observers demonstrated the citizen concerns about discolorations. Graphical abstract: fx1